2017
DOI: 10.1080/16089677.2017.1318534
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the Androgen Deficiency in Aging Male questionnaire for the clinical detection of androgen deficiency in black sub-Saharan African men with Type-2 diabetes mellitus

Abstract: Background:The Androgen Deficiency in Aging Male (ADAM) questionnaire is increasingly popular for evaluation of androgen deficiency (AD) in sub-Saharan African men with type 2 diabetes mellitus (DM). However, its reliability in this population is unknown. Methods: Total testosterone < 8 nmol/L was used as the gold standard for diagnosis of AD in this cross-sectional survey of 200 type 2 DM males aged 30-69 years. Participants also completed the Saint Louis University ADAM questionnaire whereby AD was diagnosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…The ADAM questionnaire showed adequate sensitivity but as it lacks adequate specificity we can conclude that it is not a good alternative for serum testosterone assays. This was consistent with a study conducted in Kenya which showed an 88.1% sensitivity and 44.7% specificity with 61.4% accuracy [ 10 ]. Chu et al also found similar results in the Chinese population with 86% sensitivity and 40% specificity [ 11 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The ADAM questionnaire showed adequate sensitivity but as it lacks adequate specificity we can conclude that it is not a good alternative for serum testosterone assays. This was consistent with a study conducted in Kenya which showed an 88.1% sensitivity and 44.7% specificity with 61.4% accuracy [ 10 ]. Chu et al also found similar results in the Chinese population with 86% sensitivity and 40% specificity [ 11 ].…”
Section: Discussionsupporting
confidence: 92%
“…They found that specificity for the questionnaire for reduced libido is higher compared to the specificity of the ADAM questionnaire (75.5% vs. 44.7%). Based on this finding, Ugwu et al recommended continuing using the ADAM questionnaire for screening, especially in low-income countries, as yes to the question related to loss of libido may be a good indicator for low testosterone levels [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subjects whose BP readings were ≥ 140/90 mmHg were considered hypertensive. 13 Symptoms of hypogonadism were assessed using the ADAM 14 questionnaire, which is the most widely accepted screening questionnaire consisting of 10 questions. Subjects who can read and write completed the ADAM questionnaire on their own, and those who could not were assisted by an experienced nurse.…”
Section: Demographic and Clinical Assessmentmentioning
confidence: 99%
“…Diabetes is a chronic metabolic disorder in which blood glucose levels are abnormally elevated (hyperglycemia) , and it has long been a major disease that harms human health . Insulin resistance results in damage to the tissues of the liver, muscles, fat, and other tissues involved in the regulation of blood glucose metabolism and plays a key role in type 2 diabetes (T2D) .…”
mentioning
confidence: 99%